Isolation, Identification, Resistance profile and Growth kinetics of Chlorpyrifos resistant Bacteria from Agricultural soil of Bangalore - Savitha, K.; Raman, D.N. Saraswathi (Research in Biotechnology, 2012)
Although there are benefits to the use of pesticides, there are also drawbacks, such as potential toxicity to humans and other animals and change in the ecobalance due to residual effects. The soil microflora (under persistence pesticide stress) are able to detoxify/degrade these toxic compounds into nontoxic products. Chlorpyrifos (a trichloropyridinyl phosphothioate) is one of the most widely used pesticides that exert broad based toxic effects. The present study involves the isolation,Ã‚Â identification and characterization of the chlorpyrifos resistant bacterial isolates from cabbage cultivated soil of a private agricultural farm in Bangalore, India. Out of 15 isolates 3 chlorpyrifos hyper resistant bacteria were finally selected for follow up studies. ThreeÃ‚Â isolates viz., Bacillus stearothermophilus, Bacillus circulans and Bacillus macerans were found resistant to 50mg/L, 55mg/L and 60 mg/L ofÃ‚Â chlorpyrifos.